Improvement in dyeing and physical properties of wool fabrics through pretreatment based on the bacterial culture of Stenotrophomonas maltophilia DHHJ. Issue 23 (December 2022) - Cao, Zhang-Jun; Tang, Ao; Wang, Juan; Zhang, Yun-Long; Yang, Guang; Zhang, Xing-Qun
Wool fiber is a valuable natural material in the textile industry, but keratin cuticles on its surface can deteriorate product quality. Wool fabric finishing has a long-standing problem in meeting the goal of environmental sustainability. In this study, we developed an eco-friendly simple method of wool fabric treatment based on direct incubation with the whole culture of Stenotrophomonas maltophilia DHHJ, a keratinase-producing bacterial strain. This processing method effectively reduced roughness for the surface of wool fiber and wool fabric samples by removing the cuticle scales. The keratinolytic treatment altered many physical properties of the wool fabrics, such as felting shrink, bursting strength, elongation at break, and diameter. The dyeability of wool fabric was substantially improved due to the pretreatment. The surface modification accelerated the rate of dyeing-bath exhaustion for wool fabric samples under a mild processing condition and the dyeing equilibrium was achieved within 10 min at a relatively low dyebath temperature (below 70°C). The pretreatment with the keratinase-secreting bacterial culture was beneficial for dyeing uniformity and rubbing color fastness. Besides, the fuzzing and pilling properties of wool fabrics were ameliorated in the fabric samples incubated with the bacterial culture.